P66Shc signals to age - Trinei, Mirella (Impact Journals LLC, 2009)
Oxygen metabolism is thought to impact on aging through the formation of reactive oxygen species (ROS) that are supposed to damage biological molecules. The study of p66(Shc), a crucial regulator of ROS level involved in aging dysfunction, suggests that the incidence of degenerative disease and longevity are determined by a specific signaling function of ROS other than their unspecific damaging property.